Pouzitie metódy PCR v diagnostike enterovírusových infekcií - Sojka, M; Bopegamage, S; Petrovicová, A (Epidemiologie, mikrobiologie, imunologie, 2009)
Enteroviruses belonging to the family Picornaviridae are important human pathogens. Although most cases of infection caused by these viruses are asymptomatic, a wide range of clinical syndromes is observed in manifest cases. Conventional laboratory diagnostic methods based on virus isolation and identification, or on the detection of specific antiviral antibodies, are costly and time consuming. Therefore, they are of little benefit to treatment. We have implemented a commercially available PCR-based test for the detection of enteroviral infections. In 2008, we analyzed biological specimens from 125 patients with suspected enteroviral disease, most often involving the nervous system. The presence of enterovirus was detected in 39 patients. The results were compared with those obtained by the conventional methods. PCR appeared to be a valuable method for rapid, accurate and reliable diagnosis of enteroviral infections which is of major benefit to patient management.
Keywords: RNA, Viral; RNA virová; Humans; enterovirové infekce; Serologic Tests; lidé; Myocarditis; Polymerase Chain Reaction; Enterovirus Infections; Central Nervous System Viral Diseases; polymerázová řetězová reakce; sérologické testy; Enterovirus; virové nemoci CNS; myokarditida